Grey Forecasting for technoeconomic sustainability of fiberglass composite waste recycling in developing countries - Rizwan Rasheed; Fizza Tahir; Shuaishuai Geng; Fizza Batool; Muhammad Afzaal; Yuehong Su (Heliyon)
The demand for engineered composites particularly fiberglass reinforced polymers (FRP) is gaining momentum. The manufacturing of virgin input-resins for these composites involves the use of certain materials which poses serious environmental implication. This study has exclusively applied and investigated the Grey Forecasting model for management of FRP waste in developing countries to minimize the virgin inputs and likely environmental impacts. Various recyclate-based solutions are developed, experimented and analyzed. Technoeconomic analytics projected via Grey Forecasting depicted that indigenously developed solutions of reuse and recycling of FRP waste driven via mechanical recycling are sustainable. As such a trial project in Pakistan has initiated a viable benefit-cost ratio (BCR) of 1.27 and a payback period of 26 months. Experiments using FRP recyclate-based inputs were successful in improving the filler, value, and strength of the product. As a result, consumer prices were reduced by 35 % and 21 % respectively. The recyclate material saved 15 % of the manufacturing cost as compared to the product manufactured by 100 % virgin inputs. Mechanical recycling proved as a safe and viable method that reduced the hazardous inputs by 25–28 % during manufacturing and minimizing the burden on landfills. Likewise, the mixing step focuses on eliminating the use of virgin materials and potentially harmful processes as this is where thermoset resins and glass-fibers are blended together to create the composite material. This comprehensive analysis provides a holistic perspective on policy interventions to achieve cost-effective recyclate management.